2020
DOI: 10.1021/acscatal.0c00239
|View full text |Cite
|
Sign up to set email alerts
|

Atomically Dispersed Co Catalyst for Efficient Hydrodeoxygenation of Lignin-Derived Species and Hydrogenation of Nitroaromatics

Abstract: Single-atom catalysts (SACs) have attracted much attention due to their outstanding catalytic performance in heterogeneous catalysis. Here, we report a template sacrificial method to fabricate an atomically dispersed Co catalyst; three kinds of silica templates with different microstructures (MCM-41, SBA-15, and FDU-12) were employed and the effect of pore structure of the templates on the dispersity of Co was investigated. The catalysts fabricated with different templates presented different Co dispersities, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 160 publications
(89 citation statements)
references
References 74 publications
2
87
0
Order By: Relevance
“…43 The advantage of pyridine N can be coordinated with metal atom and used as anchor points to more effectively stabilize the atomically dispersed nickel sites. 44 In Figure S8, the pyridinic-N binding energy of NC was 398.3 eV and 0.4 eV less binding energy relative to Ni-SAs/NC. We think that electron transfer occurs at the coordination of Ni and pyridine-N, caused an increase in the electron density at the center of the Ni.…”
Section: Resultsmentioning
confidence: 98%
“…43 The advantage of pyridine N can be coordinated with metal atom and used as anchor points to more effectively stabilize the atomically dispersed nickel sites. 44 In Figure S8, the pyridinic-N binding energy of NC was 398.3 eV and 0.4 eV less binding energy relative to Ni-SAs/NC. We think that electron transfer occurs at the coordination of Ni and pyridine-N, caused an increase in the electron density at the center of the Ni.…”
Section: Resultsmentioning
confidence: 98%
“…The loss in mass balance can be ascribed to the polymerization of the substrates and the formation of oligomer. [ 23 ] With methanol and isopropanol as the solvent, although the mass balance was 100%, but the yield of MMP was only 9.8% and 9.3%, respectively. Meanwhile, the conversion of vanillin was relative low and large amount of intermediate product including DMP and HMP were formed.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, various metals (e.g., Fe, Pt, Pd, Rh, Co, and Sn) based SACs were also applied in the reduction of nitro groups. [ 22,193–197 ] For example, Wang and co‐workers demonstrated that carbon‐shells‐confined Pd SAC is catalytically active to 4‐nitrophenol (4‐NP) reduction 4‐aminophenol (4‐AP) and Suzuki coupling reactions. In addition, the maximum atomic efficiency (activity platform) of the SAC can be achieved when using 4‐NP reduction as a model reaction ( Figure ).…”
Section: Applications Of Single‐atom Catalystsmentioning
confidence: 99%